2016
DOI: 10.3390/molecules21080982
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated Chalcone 2 Acts as an Antimitotic Agent and Enhances the Chemosensitivity of Tumor Cells to Paclitaxel

Abstract: Abstract:We previously reported that prenylated chalcone 2 (PC2), the O-prenyl derivative (2) of 2 1 -hydroxy-3,4,4 1 ,5,6 1 -pentamethoxychalcone (1), induced cytotoxicity of tumor cells via disruption of p53-MDM2 interaction. However, the cellular changes through which PC2 exerts its cytotoxic activity and its antitumor potential, remain to be addressed. In the present work, we aimed to (i) characterize the effect of PC2 on mitotic progression and the underlying mechanism; and to (ii) explore this informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The results obtained showed that BP-M345 has no effect on the inhibition of the p53-MDM2 interaction [ 33 ]. Thus, considering that BP-M345 possesses 3,4,5-trimethoxyphenyl groups that have been much highlighted as playing crucial role in the interaction with tubulin in MTAs, such as podophyllotoxin, combretastatin A4, and colchicine [ 38 ], as well as some chalcones previously reported as potent antimitotic agents by our group [ 38 , 39 , 40 ], it was hypothesized that this diarylpentanoid could also act as antimitotic agent.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained showed that BP-M345 has no effect on the inhibition of the p53-MDM2 interaction [ 33 ]. Thus, considering that BP-M345 possesses 3,4,5-trimethoxyphenyl groups that have been much highlighted as playing crucial role in the interaction with tubulin in MTAs, such as podophyllotoxin, combretastatin A4, and colchicine [ 38 ], as well as some chalcones previously reported as potent antimitotic agents by our group [ 38 , 39 , 40 ], it was hypothesized that this diarylpentanoid could also act as antimitotic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Also, other prenylated chalcones (e.g. O-prenyl derivative of 2′-hydroxy-3,4,4′,5,6′-pentamethoxychalcone) in combination with common anticancer drug, such as paclitaxel, have been shown to further inhibit cell growth, as determined with cell viability and proliferation assays (Fonseca et al, 2016).…”
Section: Results and Discusionmentioning
confidence: 99%
“…Different cell death mechanisms induced by these molecules have already been described, such as apoptosis mediated by caspases [ 21 , 23 ], autophagy [ 21 ], methuosis [ 24 ], and unfolded protein response mediated cell death [ 25 ]. We already reported several chalcones with promising growth inhibitory activity in human cancer cell lines [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Among these, chalcones 1 – 3 ( Figure 1 ) revealed antiproliferative activity in A375-C5 (melanoma), MCF-7 (breast adenocarcinoma), and NCI-H460 (non-small cell lung cancer) cells [ 33 ].…”
Section: Introductionmentioning
confidence: 99%